CLINICAL EVALUATION OF YOGAVASTI AND UTTARAVASTI IN VANDHYATWAM W.S.R. TO TUBAL BLOCK - A CONCEPTUAL STUDY - Anuradha Maganti (International Journal of Applied Ayurved Research, 2017)
Infertility is defined as inability to conceive even after one year, under normal marital conditions without contraception. The rate of infertility is increasing day by day with equal distribution of both male and female factors leading to unhappiness and psychosomatic illness. Besides genetic factors, changed life style, increased stress and strain and environmental pollution are identified as factors contributing to the rising rate of infertility. In the present article the problem of female infertility w.s.r to tubal block (tubal factor) has been taken for conceptual study. In Ayurveda, infertility is termed as Vandhyatwam. Vata is the predominant dosha involved in it as mentioned in our classics. According to Sushruta, tubal block can be considered as the deformity of Kshetra i.e. the female reproductive system. Very few works have been done on tubal infertility.The present article is a conceptual study on the effect of yogavasti and uttaravasti in tubal block. Erandamooladi kashayam is used for kashaya vasti and Mahanarayana tailam for matravasti and uttaravasti. Eranda comes under bhedaneeya, adhobhagahara, vatasamsamana gana, is vrushyam and contains teekshna and sukshma gunas which are very much essential for removing blocks. Mahanarayana tailam has been selected for both matravasti and uttaravasti. Most of the drugs in Mahanarayana tailam are laghu, ushna and teekshna in guna. These gunas also may be useful in bringing vata to normalcy and removing the block.